1997
DOI: 10.1089/aid.1997.13.71
|View full text |Cite
|
Sign up to set email alerts
|

CD8+T Cell Supernatants of HIV Type 1-Infected Individuals Have Opposite Effects on Long Terminal Repeat-Mediated Transcription in T Cells and Monocytes

Abstract: CD8+ T lymphocytes of HIV-1-infected individuals can efficiently suppress HIV-1 replication in CD4+ T lymphocytes via soluble factors. We compared the effect of CD8+ T cell-derived supernatants on HIV-1 LTR-driven gene expression in T cells and monocytic cell lines. Our results demonstrate that CD8+ T cell supernatants that suppressed HIV-1 LTR-driven gene expression in Jurkat T cells significantly enhanced expression in Tat-activated U38 monocytic cells in the presence and absence of mitogenic stimulation. Ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…*Pertussis toxin (PT) was used at 10 ng/ml. combination of antibodies to these chemokines abrogate the enhancement of HIV-1 replication in monocytic cells [22]. In this current work we have demonstrated that the enhancement of LTR-mediated gene expression is sensitive to PT, indicating a G protein-coupled mechanism of activation.…”
Section: Human Macrophagessupporting
confidence: 53%
See 4 more Smart Citations
“…*Pertussis toxin (PT) was used at 10 ng/ml. combination of antibodies to these chemokines abrogate the enhancement of HIV-1 replication in monocytic cells [22]. In this current work we have demonstrated that the enhancement of LTR-mediated gene expression is sensitive to PT, indicating a G protein-coupled mechanism of activation.…”
Section: Human Macrophagessupporting
confidence: 53%
“…We previously reported that while CD8 þ T cell supernatants suppress HIV-1 LTR-mediated gene expression in Jurkat T cells [18,19], an opposite effect was observed on gene expression in monocytic cells [22]. …”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations